The Morphology of Hierarchy Limasan House Space in Kertosari Ponorogo - Sari, Wahyuni Eka (University of Merdeka Malang, 2020)
Limasan house is one of the traditional houses in Java. Limasan house is a house that functions as a residence that has a unique form. Limasan house is found in Ponorogo Regency including Kertosari Village. Kertosari Village was once a batik producing center in Ponorogo Regency. The Limasan house in Kertosari Village used to function as a home to produce batik. The Limasan house which is now in Kertosari Village has started to be abandoned and neglected without any maintenance. The hierarchy of space becomes an important unit in the part of the house. Hierarchy is formed because of various factors. The purpose of this study was to find out how the morphology of the space hierarchy of the Limasan House has its unique shape. The method used is descriptive analysis with exposure to the results of field surveys. The results obtained from this study are changes from the hierarchy of space inside the Limasan house that used to be in the living room of the main building, now turning into a living room or middle room as its hierarchy.Â DOI: https://doi.org/10.26905/lw.v12i1.3615